Mathematics Curriculum Review In Junior Secondary School Level: Implementation Of Web-Based CRMS - Iin Habibah Muttaqin; Fatimah Rahmawati; Maman Fathurrohman; Cecep Anwar Hadi Firdos Santosa (Universitas Ahmad Dahlan, 2020)
This study aims to analyze the Indonesia National Curriculum (Kurikulum 2013) of mathematics at junior secondary school level. The tool used is the Web-based Curriculum Review Mapping System (CRMS). The CRMS was developed to analyze the curriculum, as expected outcome, through teachers lesson plan. The method used in this research was descriptive with a qualitative approach. In this research, the research was the main instrument assisted with interview guide sheets and documentations. The object of this research is the national curriculum for mathematics at a junior high school with three mathematics teachers as respondents to be interviewed. Analysis of the data used in the study is a qualitative analysis with three stages: data reduction, exposure, and drawing conclusions and verification. Qualitative data analysis is carried out simultaneously with data collection process. The results of the study state that the CRMS is at easy to implement by the teachers of mathematics. They can review their mathematics lesson plan using this system. Furthermore, by this system teachers could create various lesson plans.